2002
DOI: 10.1034/j.1600-0587.2002.250503.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and hen harrier productivity: from local mechanisms to geographical patterns

Abstract: Climate is an important factor limiting demography and distribution patterns in many organisms. For species with a broad geographical distribution, the mechanism by which climate influences demography is likely to vary dramatically from one end of the range to the other. In this paper we first assess, in a Scottish population of hen harriers Circus cyaneus, how temperature and rainfall influence adult behaviour and chick mortality patterns at the nest. We then test for associations between harrier productivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 24 publications
1
65
0
Order By: Relevance
“…This contrasts to what is usually observed in harrier species breeding in the Palearctic, for which the timing of breeding rarely exceeds 3 months [e.g., Pallid Harrier (Circus macrourus), Montagu's Harrier (Circus pygargus), Hen/Northern Harrier (Circus cyaneus/hudsonius), (Schipper 1979, Simmons et al 1986, Arroyo et al 1998, Simmons 2000, Amar et al 2005, Terraube et al 2009). These large scale differences in the extent of the timing of breeding are likely related to climate, the Northern Hemisphere being in general characterized by a more pronounced seasonality in rainfall and temperature regimes (Garcia and Arroyo 2001, Redpath et al 2002a) than the Southern Hemisphere, limiting in time the conditions that are suitable for successful breeding, and also suggest that conditions for breeding are suitable over a longer time for Black Harriers, as for other African raptors.…”
Section: Factors Affecting Lay Date Variationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This contrasts to what is usually observed in harrier species breeding in the Palearctic, for which the timing of breeding rarely exceeds 3 months [e.g., Pallid Harrier (Circus macrourus), Montagu's Harrier (Circus pygargus), Hen/Northern Harrier (Circus cyaneus/hudsonius), (Schipper 1979, Simmons et al 1986, Arroyo et al 1998, Simmons 2000, Amar et al 2005, Terraube et al 2009). These large scale differences in the extent of the timing of breeding are likely related to climate, the Northern Hemisphere being in general characterized by a more pronounced seasonality in rainfall and temperature regimes (Garcia and Arroyo 2001, Redpath et al 2002a) than the Southern Hemisphere, limiting in time the conditions that are suitable for successful breeding, and also suggest that conditions for breeding are suitable over a longer time for Black Harriers, as for other African raptors.…”
Section: Factors Affecting Lay Date Variationsmentioning
confidence: 99%
“…Productivity was defined as the number of young reaching 35 days of age (range 0-4) for pairs that laid a clutch. Black Harriers fledge at approximately 40 days old (Simmons et al 2005) but in many cases our last visit occurred before that age; however, in harriers, as in many other species there is usually little mortality during this late nestling stage (Redpath et al 2002a). Thus, we assume that any nestlings alive at 35 days old would have fledged.…”
Section: Breeding Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Brood age is clearly important as young broods will be more at risk from adverse weather and predators, and so will benefit from greater nest attendance (Newton 1979, Redpath et al 2002. In contrast, older chicks can thermoregulate, can better defend themselves and have higher food demands, so will benefit from an increased rate of food delivery (Houston & Davies 1985, Newton 1979.…”
mentioning
confidence: 99%
“…Moreover, early breeders have higher fitness than late breeders (Arroyo et al 2001). Some recent studies of variability in timing of breeding among mating individuals revealed other factors that are connected with geographical rate and that can initialize breeding (Redpath et al 2002). Such environmental factors include territory quality (Krüger 2002(Krüger , 2004, habitat structure (Moore 1980;Němečková 2005), or parental fitness and phenotypic quality of mating individuals (Simmons 1989;Verboven et al 2001;Childress & Bennun 2002;Krüger 2002).…”
Section: Introductionmentioning
confidence: 99%